Electronic Portfolio Use as an Assesment Medium: Pharmacy Students' Perceptions and Experiences - Lee, K.; Kinsella, M.; Oliver, Beverley; Von Konsky, Brian; Parsons, Richard (Elfel, 2010)
The roles of allied health professionals have expanded beyond traditional duties. Providers of higher education are left to find more effective methods of assessment in order to prepare graduates for these new roles. Emerging literature suggests the use of so-called ePortfolios to facilitate this graduate preparation. Curtin University in Western Australia piloted their ePortfolio system, the iPortfolio, in 2009. This system was integrated into the assessment structure of Pharmaceutical Practice 322, a third year unit in the Bachelor of Pharmacy program. The goal was to improve student learning using the iPortfolio as a medium for feedback and assessment.A study was conducted using two questionnaire-type instruments to assess students' perceptions of the iPortfolio as an assessment medium, their experience with the iPortfolio system, and whether using the iPortfolio improved the learning of course material. Each instrument collected both quantitative and qualitative data. The results and findings from both instruments were subsequently triangulated to improve the depth of understanding of the research objectives. From the data collected, it was found that whilst students were initially uncertain or negative about the implementation of the iPortfolio as an assessment medium, after 13 weeks of using the iPortfolio, they were generally enthusiastic about its use in the unit. However, regarding their experience with the iPortfolio system, students indicated that ease-of-use and ability to customise their iPortfolios were issues that needed to be addressed. Regarding the influence of the iPortfolio on learning, students indicated that they felt they were able to learn and retain more of the course material. Overall, results from this study are promising, and further studies into other applications of the iPortfolio to uncover its full potential are recommended.